KONSEP PENDIDIKAN SOSIAL DALAM ISLAM PERSPEKTIF AHMAD RAJĀB AL-ASMARĪ [736 H – 795 H] DALAM KITAB AL-NABĪ ALMURABBĪ DAN MUḤAMMAD AL-SYĀDZILĪ [1365 H – 1425 H] DALAM KITAB USUS AL-TARBIYAH AL-IJTIMĀIYAH FĪ AL-ISLĀM - Haqqi, Umar; Akmansyah, Muhammad; Amiruddin, Amiruddin (Jurnal Bilqolam Pendidikan Islam, 2024)
Human life is getting easier with new discoveries, both in the fields of science and technology. One of the advantages of this progress is that individuals get information easily and quickly, but in fact this actually increases life competition even harder. This problem can be solved by implementing social education according to Al-Qur'an and Al-Sunnah. The aim of this research is to compare and relate the concept of social education in Islam from the perspective of Ahmad Rajab Al-Asmarī and Muḥammad Al-Syādzilī. This research is library research in the form of descriptive analysis. The data is collected by using primary sources, namely the Al-Nabī Almurabbī Book and the Usus Al-Tarbiyah Al-Ijtimāiyah fī Al-Islām Book, while secondary sources are obtained through books, journals, or others that discuss research problems. Al-Asmarī emphasized the importance of the example of Prophet Muhammad as the basis for social education, while Al-Syādzilī emphasized the importance of Islamic social principles implemented through formal educational institutions and public policies. According to Al-Asmarī, social education focuses on the formation of morals and manners with the aim of forming individuals with noble character in accordance with the example of Prophet Muhammad. Meanwhile, according to Al-Syādzilī, the social education process can be used to form a just society by applying Islamic principles in all aspects of social, political and economic life. Regarding developments over time, Al-Asmarī still adheres to a traditional approach which is based on implementing established values without much modification. However, Al-Syādzilī emphasized the importance of adapting to social changes and modern challenges